Nothing can keep us together : a Gossip Girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2005)
Only two weeks remain until graduation and there are more than a few surprises in store for the senior girls at an exclusive private high school in New York City, as they fill their last days together with boys, gossip, parties, and shopping.
Keywords: Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Wealth -- Fiction; New York (N.Y.) -- Fiction